Well‐Defined Tetrazole‐Functional Copolymers as Macromolecular Ligands for Luminescent Ir(III) and Re(I) Metal Species: Synthesis, Photophysical Properties and Application in Bioimaging. Issue 11 (3rd May 2022) - Dallerba, Elena; Hartnell, David; Hackett, Mark J.; Massi, Massimiliano; Lowe, Andrew B.
Abstract: Well‐defined copolymers containing luminescent iridium and hybrid iridium/rhenium fragments are prepared utilizing parent poly( n ‐butyl acrylamide‐ co ‐ N ‐(1 H ‐tetrazol‐5‐yl) acrylamide) as macromolecular chelating species. The parent (co)polymers are prepared via the modification of a precursor poly(pentafluorophenyl acrylate) (polyPFPA) homopolymer, prepared by reversible addition‐fragmentation chain transfer polymerization, with n ‐butylamine and 5‐aminotetrazole. Reaction of the parent copolymers with [Ir2 (ppy)4 ( μ −Cl2 )] (ppy = 2‐phenylpyridine) yields modified copolymers containing the Ir(ppy)2 fragment as a pendent group. Attachment of the Ir species is confirmed by a combination of photophysical studies, UV–Vis spectroscopy, and visually under irradiation with UV light. Importantly, it is demonstrated that the chelation of the Ir(ppy)2 fragment to a polymeric scaffold does not impact the fundamental photophysical properties of the Ir species. Attachment of a second luminescent metal species, Re(CO)3 (phen) (phen = 1, 10‐phenanthroline), gives hybrid materials containing Re(I) and Ir(III). The photophysical properties of these hybrid materials are consistent with the presence of both metal species and indicate the occurrence of energy transfer phenomena from the polymer‐bound Ir to Re metal centers. Finally, it is demonstrated that the Ir modified polymers and the Ir/Re hybrid materials offer potential in tissue imaging applications with scope to tune both luminescent properties and biological specificity as evidenced from preliminary brain tissue staining experiments. Abstract : Reversible addition‐fragmentation chain transfer‐prepared, tetrazole‐functionalized copolymers are employed as macromolecular ligands for attachment of luminescent iridium(III) and rhenium(I) fragments. Detailed photophysical studies indicate that chelation to a polymeric scaffold does not affect the fundamental properties of the iridium and rhenium species. In the case of copolymers containing both metal species, there is evidence on internal energy transfer phenomena. The iridium‐based materials are shown to have potential as bioimaging agents.